Modular access to 1, 2-allenyl ketones based on a photoredox-catalysed radical-polar crossover process. Issue 39 (22nd September 2021) - Lei, Wan; Liu, Yongjun; Fang, Yewen; Li, Yan; Du, Chan; Fang, Jianghua
Abstract : New access to allenes: With photocatalytic reductive radical-polar crossover as the strategy, a new protocol for the preparation of trisubstituted allenes has been nicely developed via the reactions of 1, 3-enynes with various alkyl radicals. Abstract : Herein, a new protocol dealing with the preparation of 1, 2-allenyl ketones has been successfully developed via the reactions of enynes with radicals enabled by dual photoredox/copper catalysis. Based on the results of a deuteration experiment and the competition reaction between cyclopropanation and allenation, the mechanism based on a photoredox-neutral-catalysed radical-polar crossover process has been proposed. Synthetic applications of allenes have also been demonstrated.